Attitudes of the Portuguese population regarding dietary fibre - Guiné, Raquel (2016)
Introduction: Dietary fibre (DF) has been part of human diet for millenniums although its benefits have been recognized mainly in the last dec ades. Objectives: Because DF is such an important component of a healthy diet, the objective of this work was to evaluate the consuming habits of the Portuguese, as well as their knowledge about the fibre rich foods and their attitudes towards food labelling. Methods: A descriptive cross-sectional study was carried out on a non-probabilistic sample of 382 participants. The results showed that the ingestion of fibre rich foods like fruit, vegetables and cereals, was much lower than the recommended ingestion. Results: The results also indicated that most people do not pay the desired attention to food labelling or nutritional information. Conclusions: Also the general level of knowledge about DF was found unsatisfactory, and hence more education and efforts are necessary to inform people towards the importance of DF as part of their daily diet.